Peer mentoring in music education : developing effective student leadership - Goodrich, Andrew (Andrew McDonald) (New York : Routledge, 2023)
"Peer Mentoring in Music Education: Developing Effective Student Leadership offers a practical guide to peer mentoring in music education, enabling music teachers to implement and benefit from this technique with their students. Drawing on extensive and current research in education and music education, this book's core focus is on the instructional practice of peer mentoring and how students can become effective leaders. Through case studies and examples focused on music education, the author shows how peer mentoring can transform learning for all students and foster student leadership as part of a student-centered instructional approach. Part I explores the foundations of these instructional practices, the role of the music teacher, the role of the student, and how socializing and student leadership contribute to meaningful learning. Part II portrays stories of four exemplary music teachers who use peer mentoring and student leadership in their music programs across a wide array of age levels and music classes and ensembles. Music teachers will benefit from learning about the transformative power of peer mentoring and student leadership, and how these instructional practices aid with diversity, equity, inclusion, and access so that all students are valued in the music class and ensemble. Peer Mentoring in Music Education: Developing Effective Student Leadership provides a comprehensive guide for in-service and pre-service music teachers seeking to understand peer mentoring and incorporate this technique in teaching"--
Keywords: Music -- Instruction and study; Peer teaching; EDUCATION / Teaching Methods & Materials / Arts & Humanities; MUSIC / General